SARS-CoV-2 Treatment Approaches: Numerous Options, No Certainty for a Versatile Virus - Iacob, Simona; Iacob, Diana Gabriela (Frontiers in Pharmacology, 2020)
SARS-CoV-2 is the most recent coronavirus which crossed the species barrier in 2019 and provoked a still ongoing and dangerous pandemic known as coronavirus disease 2019 (COVID-19). The SARS-CoV-2 infection has triggered an impressive amount of clinical and experimental studies to identify an effective and safe therapy to stop the pandemic spread. Hence, numerous trials and studies have scrutinized the analogies between SARS-CoV-2 and other corona viruses or the host-virus interactions and their similarities with immune system disorders. Still, the pathogenic mechanisms behind SARS-CoV-2 have been partially deciphered and the current therapies have not yet met the initial enthusiastic expectations. So far COVID-19 therapies have targeted various pathogenic mechanisms, namely the neutralization of ACE2 receptors or SARS-CoV-2 spike protein epitopes, the disruption of the endocytic pathways using hydroxychloroquine, arbidol, or anti-Janus kinase inhibitors, the inhibition of RNA-dependent RNA polymerase using nucleotide analogues such as remdesivir, immunosuppressive drugs or molecules acting on the immune response (corticoids, interferons, monoclonal antibodies against inflammatory cytokines, mesenchymal stem cells) and convalescent plasma administration together with numerous drugs with unproven effect against SARS-CoV-2 but with potential antiviral activities (antiretrovirals, antimalarial drugs, antibiotics, etc.). Nevertheless, these therapies have been associated with side effects and contradictory results. At the same time a specific SARS-CoV-2 vaccine is a long-term solution requiring clinical validation and important investments together with appropriate strategies to promote the confidence in the safety of the new vaccine. The article revises the current state of SARS-CoV-2 therapeutic options but advises towards a more cautious and individualized treatment approach centred on the clinical features, immune particularities, and the risk-benefit balance.